2020
DOI: 10.1001/jama.2020.21115
|View full text |Cite
|
Sign up to set email alerts
|

Association of State Certificate of Need Regulation With Procedural Volume, Market Share, and Outcomes Among Medicare Beneficiaries

Abstract: IMPORTANCE Certificate of need laws provide state-level regulation of health system expenditure. These laws are intended to limit spending and control hospital expansion in order to prevent excess capacity and improve quality of care. Several states have recently introduced legislation to modify or repeal these regulations, as encouraged by executive order 13813, issued in October 2017 by the Trump administration.OBJECTIVE To evaluate the difference in markers of hospital activity and quality by state certific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…6 An additional study did not observe an association between CON status and hospital volume or quality of care in Medicare beneficiaries who underwent a range of surgical procedures from 2016-2018. 8 Though the impact of CON laws on various types of medical procedures, hospital quality, and health outcomes has been examined, we have found no studies examining hospice quality outcomes against state CON status. With the recent trends in reevaluating CON provisions, coupled with the increased need for hospice care with an aging US population, 17 lawmakers and hospice stakeholders would benefit from such data to help inform policy decisions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…6 An additional study did not observe an association between CON status and hospital volume or quality of care in Medicare beneficiaries who underwent a range of surgical procedures from 2016-2018. 8 Though the impact of CON laws on various types of medical procedures, hospital quality, and health outcomes has been examined, we have found no studies examining hospice quality outcomes against state CON status. With the recent trends in reevaluating CON provisions, coupled with the increased need for hospice care with an aging US population, 17 lawmakers and hospice stakeholders would benefit from such data to help inform policy decisions.…”
Section: Introductionmentioning
confidence: 95%
“…1,2,5,6 By 2022, some states had moved towards revising or repealing their CON laws, spurred by the 2017 executive order 13813 7 under the Trump administration which encouraged health care choice and competition across the US. 8 In addition, the COVID-19 pandemic forced states to revisit their CON statutes as they loosened provisions to expand hospital bed availability given the surge in demand. 9 Given the momentum towards loosening CON provisions, several states with CON laws impacting hospice agencies are reevaluating their positions.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies of 1990s data have reported that higher CABG mortality rates in non-CON states (Vaughan-Sarrazin et al 2002;Rosenthal and Sarrazin 2001). Related studies include (Browne et al 2018;Casp et al 2019;Ettner et al 2020;Herb et al 2021;Ohsfeldt and Li 2018;Rahman et al 2016;Schultz et al 2021;Stratmann and Wille 2016;Wu et al 2019;Yuce et al 2020;Ziino et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yet at least 9 states took steps in 2019 to modify their certificate of need rules, often because those laws are viewed as ineffective in controlling overutilization or improving quality . As Yuce and colleagues observed in this issue of JAMA , most of the literature examining the association between certificate of need and measures of utilization and patient outcomes is more than a decade old, and advances in quality measurement and improvement warrant the updated analysis that these authors undertook.…”
mentioning
confidence: 99%
“…Yuce et al 3 acknowledge that there is variation in the scope and implementation of the regulation between states that is unaccounted for in their analysis. Certificate of need programs often regulate many facilities and services besides hospitals including long-term care, outpatient surgery centers, purchases of major medical equipment, and transplant services.…”
mentioning
confidence: 99%